2021
DOI: 10.1016/j.ctrv.2021.102242
|View full text |Cite
|
Sign up to set email alerts
|

Differences in oncological and toxicity outcomes between programmed cell death-1 and programmed cell death ligand-1 inhibitors in metastatic renal cell carcinoma: A systematic review and meta-analysis

Abstract: Background:The programmed cell death ligand-1 (PD-L1)/programmed cell death-1 (PD-1) pathway is important in metastatic renal cell carcinoma (mRCC). However, some dissimilarities between anti-PD-1 and anti-PD-L1 inhibitors have emerged. We aimed to assess differences between anti-PD-1 and anti-PD-L1 combination immunotherapies as first-line treatments in mRCC patients. Methods: Multiple databases (PubMed, Web of Science, and Scopus) were searched for articles published until March 2021. Studies were eligible i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…Indeed, a much larger proportion (48%) of patients undergoing chemotherapy received subsequent ICI therapy in the KEYNOTE361 trial than in the other trials, likely contributing to the favorable OS outcomes in its chemotherapy arm as well as to the underestimation of the efficacy of pembrolizumab in patients receiving ICI therapy [12]. Moreover, it must be noted that, despite being uniformly categorized as immunotherapy, ICIs included both PD-1 and PD-L1 inhibitors, which differ in their mechanisms of action and possibly efficacy [49]. Second, while the NMA involved an indirect approach to compare outcomes from the RCTs, this approach falls short of a head-to-head comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a much larger proportion (48%) of patients undergoing chemotherapy received subsequent ICI therapy in the KEYNOTE361 trial than in the other trials, likely contributing to the favorable OS outcomes in its chemotherapy arm as well as to the underestimation of the efficacy of pembrolizumab in patients receiving ICI therapy [12]. Moreover, it must be noted that, despite being uniformly categorized as immunotherapy, ICIs included both PD-1 and PD-L1 inhibitors, which differ in their mechanisms of action and possibly efficacy [49]. Second, while the NMA involved an indirect approach to compare outcomes from the RCTs, this approach falls short of a head-to-head comparison.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PD‐L1 expression as a predictive biomarker should be elucidated in future trials. According to the other recent meta‐analysis, 22 anti‐PD‐1 agents showed superior oncological outcomes to anti‐PD‐L1 agents. Conversely, anti‐PD‐L1 agents were superior to anti‐PD‐1 agents in their safety profiles.…”
Section: Discussionmentioning
confidence: 94%
“…According to the analysis of the results of Table 3, anti-PD-1 displayed a great effect on the treatment of RCC, and anti-CTLA-4 may be close to a curtain call of clinical research. Keiichiro et al revealed that patients with metastatic RCC who received anti-PD-1 combination therapy in rst-line may obtain more bene ts than anti-PD-L1 combination therapy [35]. This still requires researchers to further explore.…”
Section: Discussionmentioning
confidence: 99%